Right ventricular free-wall longitudinal speckle tracking strain as a prognostic criterion of adverse outcomes in patients with pulmonary hypertension: a systematic review and meta-analysis - E. Z. Golukhova; I. V. Slivneva; M. L. Mamalyga; D. I. Marapov; M. N. Alekhin; I. I. Scopin; D. E. Antonova (Российский кардиологический журнал)
The absence of consensus regarding the reference values of right ventricular free wall longitudinal strain (RVFWLS) and its predictive value prompted us to conduct a systematic review and meta-analysis of publications on the predictive role of this parameter in patients with pulmonary hypertension (PH).Aim. To study the independent predictive value of RVFWLS in PH patients using 2D/3D speckle tracking echocardiography.Material and methods. Firstly, 317 publications (PubMed) and 857 Google Scholar results were selected. Of the initially identified search results, 12 articles were analyzed. The papers were cohort designed.Results. The total number of patients with PH was 1281. The mean age of patients was 54,7±6,8 years. Four studies compared the RVFWLS with a control group (n=251). The mean RVFWLS were -17,0±2,4% and -24,7±2,2% in the experimental and control groups, respectively. A meta-analysis of the difference between the mean RVFWLS values in experimental and control group patients showed its total increase in PH subjects of 8,06% (95% CI: 5,18-10,94%; p<0,00001).The total number of deaths was 268 (all-cause — 180, composite endpoint — 88). According to the meta-analysis, with an increase of 1% in RVFWLS, there is an increase in mean all-cause mortality risk by 14% (p<0,00001), as well as mean risk of adverse outcomes or PH-related events (composite endpoint) by 14% (p<0,0001).Conclusion. These results highlight the high independent predictive value of RVFWLS as a predictor of adverse outcomes or events associated with a right ventricular dysfunction progression in PH patients.